Knowledge, Attitude, and Practices of E-Banking Transactions - Tharu, Dipesh Singh; Nagarkoti, Deepa; Ayer, Amrita; Shrestha, Sushila; Khatiwada, Swikriti; Khanal, Basanta; Raya, Rajendra (Academia Journal of Research and Innovation, 2025)
This study investigates the knowledge, attitude, and practices (KAP) of e-banking users in Nepal. The main objectives were to assess consumer attitudes toward e-banking, examine the relationship between KAP components, and compare these aspects among users. Using a quantitative descriptive and comparative design based on the KAP framework, data were collected from 195 participants through an online survey. The questionnaire included sections on demographics, knowledge, attitude, and practice, with responses measured on a 5-point Likert scale. Data analysis was conducted using SPSS, employing descriptive statistics, Kendall’s tau-b correlation, and Repeated Measures ANOVA with Greenhouse-Geisser correction. Results showed that users had good knowledge of e-banking and actively practiced its use, but their attitudes were moderately positive and somewhat cautious, particularly about security and trust. Significant positive correlations existed between knowledge, attitude, and practice, indicating these factors influence one another. The ANOVA results highlighted significant differences in average scores, with knowledge and practice higher than attitude, reflecting a nonlinear trend. The sample was balanced in gender and primarily consisted of young adults with higher education. In conclusion, while Nepalese users are knowledgeable and engaged in e-banking, improving their attitudes through enhanced trust and security awareness could encourage safer and more confident use.